Policy towards sustainable development of forest sector on the principles of the green transformation of economy - Soloviy, Igor (Forestry, Forest, Paper and Woodworking Industry, 2024)
The development of scientific thought, aimed at both environmentally friendly and socialy just harmonization of economic activity is reflected in contemporary scientific theories, which are institutionalized in such disciplines as ecological economics, environmental economics, green economics, physical economy, and others. The ideas of greening of economy become popular and are recognized finally at the highest political level. The approach to building "green economy", proposed in a number of UNEP reports is based on selection of key sectors to the transformation which are critical for the greening of the global economy. Forestry is n one of the ten classifiedas areas as key sectors . Therefore, forest sector at the global and national levels is facing the challenges that may be key in determining the future trajectories of forest policy development. Policy initiatives aimed at achieving ecological transformation of the economy opens up new opportunities for forest sector, but at the same time they require adjustment of forest policy and new innovative strategic approaches.